Amphiphilic metallosurfactants as potential scaffolds for facile fabrication of PdO-NiO nanocomposites for environmentally benign synthesis of xanthene derivatives. (December 2019) - Kaur, N.; Dhairwal, P.; Brar, A.; Kaur, G.; Bhalla, A.; Prakash, C.; Chaudhary, G.R.
Abstract: The present report focuses on a novel approach for the synthesis of mixed metal oxide nanocomposites (NCs), i.e. PdO-NiO NCs using double-chained amine-based metallosurfactants of type [M(C12 H25 NH2 )2 ]Cl2, where M represents Pd and Ni. The adopted methodology involving metallosurfactants yields highly crystalline PdO-NiO NCs with size range 10–20 nm and confirmed through X-ray diffraction and high-resolution transmission electron microscopy. Elemental mapping and X-ray photoelectron spectroscopy suggest the elemental distribution and oxidation states of the metals in the NC. Furthermore, the as-synthesized NC has been evaluated for its catalytic activity in the synthesis of pharmaceutically important xanthene derivatives using microwaves as energy source. Under optimized reaction conditions, very good product yields have been obtained in shorter reaction times. The rate constant of the catalytic reaction has been calculated through the kinetic studies, which have been reported for the first time. The second–order reaction kinetics establishes the two-step reaction mechanism, which has been found to be in agreement with the mechanism proposed in the literature. The key features like high catalytic activity, recycling efficiency and easy fabrication of PdO-NiO NCs promote this catalytic system as a potential alternative in developing environment friendly, industrially viable and energy efficient catalytic systems. Graphical abstract: Image 1 Highlights: Synthesis of PdO-NiO nanoparticles (NPs) using metallosurfactants as precursors. Remarkable catalytic activity in the synthesis of xanthene derivatives. Energy efficient and benign reaction conditions using microwaves in solvent-free conditions. Mechanistic and kinetic studies to determine rate constant for the catalytic reaction. Good recyclability for over seven usage cycles.